The Use of Prompt Engineering in ChatGPT to Improve the Ability to Write Ethnoliteracy-Based Fiction Stories in Elementary Schools: A Quasi-Experimental Study - Fauzi, Muhammad Rizal; Nurani, Riga Zahara; Ruqoyyah, Siti; Muftianti, Agni; Palupiningsih, Angesti (Universitas Negeri Makassar, 2025)
This study aims to improve the ability to write ethnoliteracy-based fiction stories through the use of GPT chat engineering prompts in 5th grade elementary school students. This study employed a quasi-experimental nonequivalent control group design involving 50 students, divided into an experimental and a control group. The experimental group participated in fiction writing learning using ChatGPT with structured prompting tasks that highlight folklore and local cultural values, while the control group participated in conventional learning. The research instrument was a pre- and post-treatment ethnoliteracy-based fiction story writing test, with assessments that included indicators of writing fiction stories and the integration of local cultural elements. The results showed a statistically significant increase in the experimental group, especially in the ability to insert cultural values meaningfully in the story, this is because there are implications through the process of learning to write ethnoliteracy-based fiction stories that students are stimulated through chatGPT prompting learning. These findings indicate that prompt engineering with the help of ChatGPT can be an effective pedagogical strategy and have an impact on students' culturally responsive and creative writing learning at the elementary school level, thus making students more creative in utilizing the capabilities of GPT chat prompt engineering as a stimulation to brainstorm new ideas in honing and developing their ability to write fiction stories optimally.